Overcoming Regulatory Failure in the Design and Implementation of Gas Flaring Policies: The Potential and Promise of an Energy Justice Approach - Aare Afe Babalola (19488253) (2022)
Gas flaring is a major source of air pollution and a chief contributor to climate change. Addressing the adverse social, environmental, and economic impacts of gas flaring has therefore been identified as a fundamental objective of energy policy in oil- and gas-producing countries across the world. Despite this recognition however, gas flaring remains a significant threat to energy justice worldwide, especially in resource-rich Middle Eastern and African (MEA) countries. In Nigeria, for example, as far back as 1979, the primary legislation fixed 1 January 1984 as the deadline for all energy operators to stop gas flaring. More than three decades later, Nigeria remains one of the highest gas flaring countries on earth, with significant adverse social, environmental, and human rights impacts on local communities. While a number of existing studies have documented the perennial failure of gas flaring regulation and policies in Nigeria and other MEA countries, a detailed examination of the energy justice gaps that limit the design and implementation of gas flaring reduction policies has remained absent. This article fills a gap in this regard. Drawing lessons from Nigeria, this article analyzes the energy justice dimensions of regulatory failure in the design and implementation of gas flaring policies. Various legal and institutional drivers of regulatory failures in gas flaring reduction policies are examined in order to identify the ways in which an energy justice governance framework can help close these gaps. The study suggests that conceptualizing and elaborating the energy justice dimensions of gas flaring in energy policy design, enacting stringent and coherent gas flaring legislation, promoting the transparent reporting and disclosure of statistical data on gas flaring reduction programs, and reforming regulatory institutions to ensure coherent implementation of gas flaring policies are significant steps towards overcoming regulatory failure in the design and implementation of energy policies on gas flaring reduction. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14116800